A preparation method of a flame-retardant anti-static canvas base material fiber impregnated coating modification
Patent Information
- Application Number
- CN202611370518.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种阻燃防静电帆布基材纤维浸渍包覆改性制备方法,解决了现有改性工艺中改性组分易发生热泳移分布不均、原位聚合放热致使聚合物氧化降解,以及多组分浸渍体系易破乳团聚导致产品性能不稳定且耐洗涤性差的问题
[0050] 1. This invention establishes a liquid-phase buffer zone within the fiber by controlling the liquid content of the canvas after impregnation and utilizing the high-humidity steam environment in a continuous steam chamber. This treatment reduces the rate of moisture evaporation and diffusion to the surface, helping to mitigate the migration effect caused by solutes migrating with moisture. This allows monomers and dopants to polymerize in situ within the fiber, improving the uniformity of the modified components' distribution on the fabric surface. Simultaneously, the liquid-phase region absorbs the exothermic reaction generated during polymerization, helping to control the system temperature, reduce polymer oxidative degradation caused by localized overheating, and maintain the stability of the material's antistatic properties.
Smart Images

Figure CN122918841A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile modification technology, specifically to a method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification. Background Technology
[0002] Industrial canvas is widely used in environments such as coal mining, chemical production, and dusty operations. Because these environments present flammable and explosive risks, the static electricity generated by friction on the canvas can easily lead to safety accidents. Therefore, the substrate typically requires flame-retardant and anti-static modification treatment.
[0003] Currently, a process combining impregnation and in-situ polymerization is commonly used to modify canvas. This involves synthesizing conductive polymers in situ on the fiber substrate surface and combining them with flame retardants to achieve multiple functions. However, this process has some technical drawbacks in actual manufacturing. During the drying or thermal polymerization stage of the aqueous working solution, the rapid evaporation of water to the fiber surface can cause monomers or modifying agents in the liquid phase to migrate outwards. This thermophoresis phenomenon can easily lead to uneven distribution of the modified components on the canvas. Furthermore, the in-situ synthesis reaction of conductive polymers is usually accompanied by a significant exothermic process. Conventional padding and finishing processes lack effective local temperature buffering mechanisms, and local overheating can easily cause excessive oxidative degradation of the newly formed polymer backbone, resulting in damage to the material's conductivity.
[0004] To balance flame retardancy, conductivity, and film adhesion of the modified components, the impregnation solution is typically a blend of various functional additives and film-forming emulsions. These blended systems often contain ionic substances with different charges. Under mixed conditions or subsequent acidic or oxidizing reactions, electrostatic interactions easily occur between the components, leading to charge neutralization and consequently flocculation, aggregation, or demulsification of the working solution. The instability of the impregnation system makes it difficult for the active ingredients to form a continuous and firmly adhered coating layer on the surface of the fiber monofilaments. This results in fluctuations in the flame retardant and antistatic properties of the final modified canvas, and poor washability during use.
[0005] Therefore, this invention proposes a method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification to overcome the shortcomings of the prior art. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification. This method solves the problems in existing modification processes, such as uneven distribution of modified components due to thermophoresis, in-situ polymerization exothermic leading to polymer oxidative degradation, and the tendency of multi-component impregnation systems to demulsify and agglomerate, resulting in unstable product performance and poor washability.
[0007] To achieve the above objectives, the present invention provides a method for preparing a flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification, comprising the following steps:
[0008] Sodium lignosulfonate, phytic acid aqueous solution, aniline, aliphatic nonionic waterborne polyurethane emulsion and deionized water are mixed evenly to obtain the main impregnation solution.
[0009] Ammonium persulfate was dissolved in deionized water to obtain an initiator aqueous solution;
[0010] The canvas is continuously and flatly passed through the main impregnation liquid for immersion and then squeezed through a rolling mill to control the liquid content.
[0011] The canvas, after being squeezed by the rolling mill, is introduced into a continuous steam chamber. Under the condition of steam, the initiator aqueous solution is atomized into droplets and sprayed onto the surface of the canvas to carry out an in-situ oxidative polymerization reaction.
[0012] The canvas that has completed in-situ polymerization is introduced into a hot air tenter frame for drying and film formation, and then wound up after cooling.
[0013] By adopting the above technical solution, the combination of in-situ oxidative polymerization and specific modified components, along with continuous steaming and atomized spraying processes, helps to improve the stability and uniformity of the flame retardant and antistatic properties of the modified canvas.
[0014] In constructing the impregnation system, an aliphatic nonionic aqueous polyurethane emulsion was selected as the film-forming matrix. Because the nonionic polyurethane backbone is uncharged, it is less likely to undergo electrostatic interactions with the anions of phytic acid, sodium lignosulfonate, ammonium persulfate, and the cationic polyaniline generated during the mixing process. This nonionic property, to a certain extent, inhibits flocculation or demulsification of the mixture, helping to maintain the homogeneous stability of the main impregnation solution at room temperature.
[0015] In the in-situ polymerization stage, the initiator ammonium persulfate is sprayed onto the canvas surface impregnated with the main impregnation solution via atomization, and oxidative polymerization is carried out in a steam environment with the temperature and relative humidity provided by a continuous steam chamber. Specifically, ammonium persulfate dissociates in the aqueous phase to generate sulfate radicals, which oxidize the aniline monomers on the canvas surface, causing them to lose electrons and generate aniline radical cations. Subsequently, these aniline radical cations undergo para-coupling to form dimers, and further deprotonate to continue coupling with monomer radicals, generating a polyaniline backbone. At the same time, because the phytic acid molecule contains phosphate groups, the hydrogen ions ionized in the aqueous medium protonate and dope the imine nitrogen atoms on the newly generated polyaniline backbone, causing the polyaniline to change from an insulating intrinsic state to a conductive polaron state, generating a phytic acid-doped polaron state polyaniline composite.
[0016] To address the migration phenomenon caused by the rapid evaporation of moisture onto the fiber surface during conventional drying polymerization, which leads to solute migration, this solution utilizes the liquid phase volume retained in the impregnated canvas to complement the steam in the steam chamber, forming a liquid-phase buffer zone. The higher relative humidity reduces the rate of moisture evaporation and diffusion from the fiber interior, promoting better fixation of monomers, dopants, and polyurethane particles in their initial positions within the fiber for reaction. Simultaneously, due to the exothermic reaction in aniline polymerization, the liquid-phase buffer zone possesses a certain specific heat capacity, absorbing some of the reaction heat generated during polymerization. This helps maintain a stable system temperature, thereby reducing excessive oxidative degradation of the polyaniline backbone due to localized overheating and preserving good electrical conductivity.
[0017] In the subsequent hot air drying film-forming stage, as moisture evaporates, the nonionic waterborne polyurethane particles fuse together to form a continuous polymer film on the fiber surface. This polyurethane film can coat and solidify the in-situ generated phytic acid-doped polyaniline and sodium lignosulfonate onto the fiber matrix, constructing a conductive network at the fiber monofilament level. Furthermore, when the material is heated and burned, phytic acid provides an acid source to catalyze dehydration, polyurethane and polyaniline act as gas sources to release non-combustible gases and promote the expansion of the carbon layer, while sodium lignosulfonate provides a carbon source to form the basic carbon framework. The three combine to form a phosphorus-nitrogen-carbon synergistic expanding flame-retardant char layer, thereby blocking the transfer of oxygen and heat.
[0018] Preferably, the main impregnation solution is prepared by mixing raw materials comprising the following parts by weight:
[0019] Sodium lignosulfonate 3.0-5.0 parts; phytic acid aqueous solution 6.0-10.0 parts; aniline 3.0-5.0 parts; aliphatic nonionic waterborne polyurethane emulsion 15.0-20.0 parts; deionized water 60.0-73.0 parts;
[0020] The initiator aqueous solution is prepared by mixing the following raw materials in parts by weight: 30.0-40.0 parts ammonium persulfate; 60.0-70.0 parts deionized water.
[0021] By adopting the above technical solution, the mass ratio of each reaction component to the initiator is limited. Sodium lignosulfonate provides dispersion ability and the basis for subsequent char formation; the amount of phytic acid can meet the doping requirements of aniline monomer to achieve antistatic properties, and ensure that the phosphorus content of the polyurethane film meets the flame retardant requirements; the proportion of nonionic waterborne polyurethane is used to adjust the feel of the fabric and the strength of the coating bond.
[0022] Preferably, the phytic acid aqueous solution contains 50 wt% phytic acid.
[0023] The canvas is an industrial canvas made of pitch-based chopped carbon fiber and flame-retardant polyester fiber, with a basis weight of 600-1200 g / m². 2 .
[0024] By adopting the above technical solution, the acidity of the main impregnation solution is controlled by a phytic acid aqueous solution of a specified concentration, so as to reduce the possibility of premature side reactions in the reaction system; by using a mixed fiber of carbon fiber and flame-retardant polyester fiber as the substrate, the basic mechanical strength and preliminary flame-retardant ability of the substrate itself are utilized, and after being combined with the in-situ generated coating modification layer, the overall mechanical properties and flame-retardant level of the product are improved.
[0025] Preferably, the aliphatic nonionic aqueous polyurethane emulsion is prepared from raw materials comprising the following parts by weight:
[0026] 45.0-55.0 parts of polycarbonate diol;
[0027] 10.0-20.0 parts of polyethylene glycol;
[0028] Isophorone diisocyanate 16.7-22.2 parts;
[0029] 0.04-0.06 parts of dibutyltin dilaurate;
[0030] 3.5-5.3 parts of 1,4-butanediol;
[0031] 340.8-370.0 parts of deionized water.
[0032] By employing the above technical solution, using polycarbonate diol and isophorone diisocyanate as the main reacting monomers, the resulting polyurethane film possesses certain resistance to UV yellowing and mechanical strength. The introduction of polyethylene glycol provides hydrophilic segments, endowing the polyurethane emulsion with nonionic hydrophilic characteristics. This eliminates the need for salt-forming reactions using small-molecule amine neutralizing agents, thus removing ionic emulsifying groups from the polymer molecular chain. This helps enhance the stability of the polyurethane emulsion in acidic and oxidizing environments, reducing emulsion aggregation caused by charge neutralization.
[0033] Preferably, the preparation method of the aliphatic nonionic waterborne polyurethane emulsion includes the following steps:
[0034] The polycarbonate diol and the polyethylene glycol are added to a reaction vessel and dehydrated under vacuum at 100-110°C for 1-2 hours.
[0035] Cool to 60-65℃, add the isophorone diisocyanate, then heat to 75-85℃, add the dibutyltin dilaurate dropwise, and react at a constant temperature for 2-3 hours;
[0036] The temperature was lowered to 40-50℃, and the 1,4-butanediol was added to carry out a chain extension reaction for 1-1.5 hours. During the addition of the deionized water, a high shear dispersion of 2000-3000 rpm was maintained. The deionized water was slowly added and reverse emulsification was carried out. The dispersion was continued for 30-45 minutes to obtain an aliphatic nonionic waterborne polyurethane emulsion with a solid content of 20wt%.
[0037] By employing the above technical solution, the temperature and time parameters during the reaction process are controlled to maintain the molecular weight distribution of the polyurethane prepolymer within a reasonable range. High-shear dispersion is used to disperse the polymer in the aqueous phase, achieving phase-conversion emulsification without the addition of external ionic emulsifiers, resulting in a nonionic waterborne polyurethane emulsion with uniform particle size.
[0038] Preferably, when preparing the main impregnation solution, mechanical stirring is turned on at a temperature of 20-25°C, the speed is set to 300-500 rpm, and the mixture is continuously mixed for 30-45 minutes.
[0039] When preparing the initiator aqueous solution, it is stirred and dissolved at room temperature in the dark to form a homogeneous transparent liquid.
[0040] By adopting the above technical solution, the impregnation liquid is mixed under the set temperature and mechanical shear force to promote the uniform distribution of monomers and additives between the aqueous phase and polyurethane latex particles; the initiator aqueous solution is dissolved in the dark mainly to reduce the premature decomposition of ammonium persulfate under light conditions and to maintain its oxidative activity as much as possible until the vapor polymerization stage.
[0041] Preferably, the linear speed for impregnating the canvas is set to 10-15 m / min, and the impregnation temperature is controlled at 20-25℃; by adjusting the linear pressure of the rollers, the liquid content of the canvas is controlled at 75%-85%.
[0042] By adopting the above technical solution, the padding process is carried out at room temperature, which reduces the probability of premature self-polymerization of monomers in the padding tank; the liquid carry-over ratio parameter provides liquid phase reaction space for in-situ polymerization. Too low a liquid volume will cause the polymerization medium to dry out and affect the reaction, while too high a liquid volume will reduce the polymerization concentration and increase the energy consumption of the hot air drying process.
[0043] Preferably, direct steam is introduced into the continuous steam chamber, the temperature is maintained at 45-50℃, and the relative humidity is kept constant at 98%-100%; the residence time of the canvas in the steam chamber is set to 5-8 minutes.
[0044] By adopting the above technical solution, the set steam temperature meets the activation energy conditions required for ammonium persulfate to initiate polymerization, while avoiding structural defects in polyaniline caused by excessively high temperatures; a relative humidity of 98%-100% is used to suppress the evaporation of water in the main impregnation solution and alleviate the migration effect; the residence time ensures that the in-situ polymerization reaction reaches the corresponding monomer conversion rate.
[0045] Preferably, when the initiator aqueous solution is atomized into droplets and sprayed onto the canvas surface, it is done through polytetrafluoroethylene airflow atomizing nozzles distributed above and below the canvas running trajectory. The atomization operation pressure is set to 0.2-0.3 MPa, and the atomized droplet particle size is controlled to be 10-50 μm. The spraying amount of the initiator aqueous solution is adjusted to 18%-25% of the dry fabric mass.
[0046] By adopting the above technical solution, the initiator aqueous solution is broken into fine droplets by airflow atomization. After the droplets contact the canvas, they penetrate the fabric surface and enter the pores between the fiber monofilaments, so that the initiator and the main impregnation solution are in uniform contact on the fiber surface and inside, which is beneficial to improve the uniformity of in-situ polymerization. The PTFE nozzle reduces the risk of corrosion of the equipment by the initiator.
[0047] Preferably, during the drying and film formation process in the hot air tenter frame, the temperature of the hot air zone is set to 120-130℃, and the canvas dwell time is 3-5 minutes; after cooling and winding, a cooling roller with a surface temperature of 15-20℃ is used for contact cooling, and constant tension winding is performed.
[0048] By employing the above technical solution, residual moisture in the system is removed at 120-130℃, causing the waterborne polyurethane latex particles to deform and cross-link to form a film, thus solidifying the conductive and flame-retardant components onto the substrate. The contact cooling method lowers the fabric surface temperature, facilitating the release of thermal stress during the cooling process of the polymer material and maintaining the dimensional stability of the canvas.
[0049] This invention provides a method for preparing a flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification. It has the following beneficial effects:
[0050] 1. This invention establishes a liquid-phase buffer zone within the fiber by controlling the liquid content of the canvas after impregnation and utilizing the high-humidity steam environment in a continuous steam chamber. This treatment reduces the rate of moisture evaporation and diffusion to the surface, helping to mitigate the migration effect caused by solutes migrating with moisture. This allows monomers and dopants to polymerize in situ within the fiber, improving the uniformity of the modified components' distribution on the fabric surface. Simultaneously, the liquid-phase region absorbs the exothermic reaction generated during polymerization, helping to control the system temperature, reduce polymer oxidative degradation caused by localized overheating, and maintain the stability of the material's antistatic properties.
[0051] 2. This invention utilizes the synergistic effect of in-situ oxidative polymerization and nonionic waterborne polyurethane emulsion to construct a cross-linked coating structure at the fiber monofilament level. During the drying and film-forming stage, the polyurethane film solidifies phytic acid-doped polyaniline and sodium lignosulfonate onto the substrate surface, improving the adhesion and washability between the modified components and the fibers. When the material is heated, the components work together to form a phosphorus-nitrogen-carbon synergistic expanded carbon layer, which provides conductive channels to release static electricity while also blocking oxygen and heat transfer.
[0052] 3. This invention utilizes the physical property that its molecular backbone is uncharged by selecting an aliphatic nonionic aqueous polyurethane emulsion as the film-forming matrix to prepare the main impregnation solution. This makes it less likely for the polyurethane components to generate electrostatic interactions with the anions of phytic acid and sodium lignosulfonate, as well as the in-situ generated polyaniline cations, during the mixing and reaction stages. This reduces the probability of charge neutralization in the multi-component composite system, which could lead to flocculation or demulsification, and helps maintain the homogeneous stability of the complex impregnation system at room temperature. Attached Figure Description
[0053] Figure 1 This is a graph showing the change in apparent viscosity of the main impregnation solution of the present invention at 25°C over standing time.
[0054] Figure 2 Figure 1 shows the characterization results of the modified layer powder of the present invention. (a) is the Fourier transform infrared spectrum of the modified layer powder of Example 2, and (b) is the thermogravimetric analysis curve of the modified layer powders of Example 2, Comparative Example 6 and Comparative Example 7 under nitrogen atmosphere. Detailed Implementation
[0055] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0056] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0057] Heavy-duty industrial canvas made of pitch-based chopped carbon fiber and flame-retardant polyester fiber, commercially available industrial grade, weight 600g / m². 2 800g / m 2 Or 1200g / m 2 The specific weight is selected according to the conditions described in each embodiment.
[0058] Sodium lignosulfonate, CAS No. 8061-51-6, commercially available industrial grade, with a weight-average molecular weight (Mw) of 8000 g / mol to 10000 g / mol and a pH value of 7.0 to 9.0.
[0059] Phytic acid, CAS No. 83-86-3, commercially available analytical grade, provided as a 50 wt% aqueous solution.
[0060] Aniline, CAS number 62-53-3, commercially available analytical grade, with a purity of not less than 99.5%.
[0061] Ammonium persulfate, CAS No. 7727-54-0, commercially available analytical grade, purity not less than 98.0%.
[0062] Polycarbonate diol, commercially available industrial grade, with a number average molecular weight (Mn) of 2000 g / mol and a hydroxyl value of 54 mg KOH / g to 58 mg KOH / g.
[0063] Polyethylene glycol, CAS number 25322-68-3, commercially available analytical grade, with an average molecular weight of 1500 g / mol.
[0064] Isophorone diisocyanate, CAS No. 4098-71-9, commercially available analytical grade, purity not less than 99.0%.
[0065] Dibutyltin dilaurate, CAS No. 77-58-7, commercially available analytical grade.
[0066] 1,4-Butanediol, CAS No. 110-63-4, commercially available analytical grade, purity not less than 99.0%.
[0067] Preparation Example 1:
[0068] This preparation example provides a method for preparing an aliphatic nonionic aqueous polyurethane emulsion, including the following steps:
[0069] 55.0 parts by weight of polycarbonate diol and 10.0 parts by weight of polyethylene glycol were added to a four-necked flask equipped with a mechanical stirrer, a condenser and a nitrogen protection device, and the mixture was dehydrated under vacuum at 100°C for 1 hour.
[0070] Cool to 60°C, add 16.7 parts by weight of isophorone diisocyanate, then heat to 75°C, add 0.04 parts by weight of dibutyltin dilaurate, and react at a constant temperature for 2 hours.
[0071] The temperature was lowered to 40°C, and 3.5 parts by weight of 1,4-butanediol were added to carry out chain extension reaction for 1 hour. Under high shear dispersion at 2000 rpm, 340.8 parts by weight of deionized water were slowly added to carry out reverse emulsification and dispersed for 30 minutes to obtain an aliphatic nonionic waterborne polyurethane emulsion with a solid content of 20 wt%.
[0072] Preparation Example 2:
[0073] This preparation example provides a method for preparing an aliphatic nonionic aqueous polyurethane emulsion, including the following steps:
[0074] Add 50.0 parts by weight of polycarbonate diol and 15.0 parts by weight of polyethylene glycol to a four-necked flask equipped with a mechanical stirrer, a condenser and a nitrogen protection device, and dehydrate under vacuum at 105°C for 1.5 hours.
[0075] The temperature was lowered to 62°C, and 19.5 parts by weight of isophorone diisocyanate were added. Then the temperature was raised to 80°C, and 0.05 parts by weight of dibutyltin dilaurate were added dropwise. The reaction was carried out at a constant temperature for 2.5 hours. The temperature was lowered to 45°C, and 4.4 parts by weight of 1,4-butanediol were added to carry out a chain extension reaction for 1.2 hours.
[0076] Under high shear dispersion at 2500 rpm, 355.6 parts by weight of deionized water were slowly added for reverse emulsification, and the dispersion was continued for 40 minutes to obtain an aliphatic nonionic waterborne polyurethane emulsion with a solid content of 20 wt%.
[0077] Preparation Example 3:
[0078] This preparation example provides a method for preparing an aliphatic nonionic aqueous polyurethane emulsion, including the following steps:
[0079] 45.0 parts by weight of polycarbonate diol and 20.0 parts by weight of polyethylene glycol were added to a four-necked flask equipped with a mechanical stirrer, a condenser and a nitrogen protection device, and the mixture was dehydrated under vacuum at 110°C for 2 hours.
[0080] The temperature was lowered to 65°C, and 22.2 parts by weight of isophorone diisocyanate were added. Then the temperature was raised to 85°C, and 0.06 parts by weight of dibutyltin dilaurate were added dropwise. The reaction was carried out at a constant temperature for 3 hours. The temperature was lowered to 50°C, and 5.3 parts by weight of 1,4-butanediol were added to carry out a chain extension reaction for 1.5 hours.
[0081] Under high shear dispersion at 3000 rpm, 370.0 parts by weight of deionized water were slowly added for reverse emulsification, and the mixture was continuously dispersed for 45 minutes to obtain an aliphatic nonionic waterborne polyurethane emulsion with a solid content of 20 wt%.
[0082] Example 1:
[0083] This embodiment provides a method for preparing a flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification, including the following steps:
[0084] Preparation of the main impregnation solution: At a temperature of 20°C, 3.0 parts by weight of sodium lignosulfonate, 6.0 parts by weight of phytic acid (50 wt% aqueous solution), 3.0 parts by weight of aniline, 15.0 parts by weight of the aliphatic nonionic aqueous polyurethane emulsion obtained in Preparation Example 1, and 73.0 parts by weight of deionized water were added to the mixing tank in sequence; mechanical stirring was turned on and the speed was set to 300 rpm, and the mixture was continuously mixed for 30 minutes to form a uniform and stable main impregnation solution, which was then conveyed to the padding tank.
[0085] Preparation of initiator aqueous solution: Dissolve 30.0 parts by weight of ammonium persulfate and 70.0 parts by weight of deionized water at room temperature in the dark by stirring to form a homogeneous transparent liquid, and then deliver it to the atomization supply pipeline of the steam box.
[0086] Room temperature padding and liquid carryover rate control: Take a basis weight of 600 g / m 2 The pitch-based chopped carbon fiber and flame-retardant polyester fiber blended industrial canvas is continuously passed through a padding tank at a temperature of 20°C at a linear speed of 10 m / min. After exiting the tank, it passes through a two-roll mill, and the linear pressure of the rolls is adjusted to control the liquid content of the canvas at 75%.
[0087] In-situ oxidative polymerization initiated by atomization under saturated steam environment: The canvas, after being extruded by a rolling mill, is continuously introduced into a continuous steam chamber; direct steam is introduced into the chamber, the temperature is maintained at 45℃, and the relative humidity is kept constant at 98%; through polytetrafluoroethylene (PTFE) atomizing nozzles distributed above and below the canvas running track, the initiator aqueous solution is atomized into droplets with a particle size of 10μm at an operating pressure of 0.2MPa and sprayed onto both sides of the canvas; the spray flow rate is adjusted so that the amount of initiator aqueous solution sprayed is 18% of the dry fabric mass; the residence time of the canvas in the steam chamber is set to 5 minutes.
[0088] Hot air drying to form film, stretching and winding: The canvas is introduced into the hot air stretching and winding machine, the temperature of the hot air zone is set to 120℃, and the dwell time is 3 minutes; finally, after being cooled by the cooling roller with a surface temperature of 15℃, it is wound up under constant tension.
[0089] Example 2:
[0090] This embodiment provides a method for preparing a flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification, including the following steps:
[0091] Preparation of the main impregnation solution: At a temperature of 22°C, 4.0 parts by weight of sodium lignosulfonate, 8.0 parts by weight of phytic acid (50 wt% aqueous solution), 4.0 parts by weight of aniline, 17.5 parts by weight of the aliphatic nonionic aqueous polyurethane emulsion obtained in Preparation Example 2, and 66.5 parts by weight of deionized water were added to the mixing tank in sequence; mechanical stirring was turned on and the speed was set to 400 rpm, and the mixture was continuously mixed for 40 minutes to form a uniform and stable main impregnation solution, which was then conveyed to the padding tank.
[0092] Preparation of initiator aqueous solution: Dissolve 35.0 parts by weight of ammonium persulfate and 65.0 parts by weight of deionized water at room temperature in the dark by stirring to form a homogeneous transparent liquid, and then deliver it to the atomization supply pipeline of the steam box.
[0093] Room temperature padding and liquid carryover rate control: Take a basis weight of 800 g / m 2 The pitch-based chopped carbon fiber and flame-retardant polyester fiber blended industrial canvas is continuously passed through an impregnation tank at a temperature of 22°C at a linear speed of 12 m / min. After exiting the tank, it passes through a two-roll mill, and the linear pressure of the rolls is adjusted to control the liquid content of the canvas at 80%.
[0094] In-situ oxidative polymerization initiated by atomization under saturated steam environment: The canvas, after being extruded by a rolling mill, is continuously introduced into a continuous steam chamber; direct steam is introduced into the chamber, the temperature is maintained at 48℃, and the relative humidity is kept constant at 100%; through polytetrafluoroethylene (PTFE) atomizing nozzles distributed above and below the canvas running track, the initiator aqueous solution is atomized into droplets with a particle size of 30μm at an operating pressure of 0.25MPa and sprayed onto both sides of the canvas; the spray flow rate is adjusted so that the amount of initiator aqueous solution sprayed is 22% of the dry fabric mass; the residence time of the canvas in the steam chamber is set to 6 minutes.
[0095] Hot air drying to form film, stretching and winding: The canvas is introduced into the hot air stretching and winding machine, the temperature of the hot air zone is set to 125℃, and the dwell time is 4 minutes; finally, after being cooled by the cooling roller with a surface temperature of 18℃, it is wound up under constant tension.
[0096] Example 3:
[0097] This embodiment provides a method for preparing a flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification, including the following steps:
[0098] Preparation of the main impregnation solution: At a temperature of 25°C, 5.0 parts by weight of sodium lignosulfonate, 10.0 parts by weight of phytic acid (50 wt% aqueous solution), 5.0 parts by weight of aniline, 20.0 parts by weight of the aliphatic nonionic aqueous polyurethane emulsion obtained in Preparation Example 3, and 60.0 parts by weight of deionized water were added to the mixing tank in sequence; mechanical stirring was turned on and the speed was set to 500 rpm, and the mixture was continuously mixed for 45 minutes to form a uniform and stable main impregnation solution, which was then conveyed to the padding tank.
[0099] Preparation of initiator aqueous solution: Dissolve 40.0 parts by weight of ammonium persulfate and 60.0 parts by weight of deionized water at room temperature in the dark by stirring to form a homogeneous transparent liquid, and then deliver it to the atomization supply pipeline of the steam box.
[0100] Room temperature padding and liquid carryover rate control: take a basis weight of 1200 g / m 2 The pitch-based chopped carbon fiber and flame-retardant polyester fiber blended industrial canvas is continuously passed through a padding tank at a temperature of 25°C at a linear speed of 15 m / min. After exiting the tank, it passes through a two-roll mill, and the linear pressure of the rolls is adjusted to control the liquid content of the canvas at 85%.
[0101] In-situ oxidative polymerization initiated by atomization under saturated steam environment: The canvas, after being extruded by a rolling mill, is continuously introduced into a continuous steam chamber; direct steam is introduced into the chamber, the temperature is maintained at 50℃, and the relative humidity is kept constant at 100%; through polytetrafluoroethylene (PTFE) atomizing nozzles distributed above and below the canvas running track, the initiator aqueous solution is atomized into droplets with a particle size of 50μm at an operating pressure of 0.3MPa and sprayed onto both sides of the canvas; the spray flow rate is adjusted so that the amount of initiator aqueous solution sprayed is 25% of the dry fabric mass; the residence time of the canvas in the steam chamber is set to 8 minutes.
[0102] Hot air drying to form film, stretching and winding: The canvas is introduced into the hot air stretching and winding machine, the temperature of the hot air zone is set to 130℃, and the dwell time is 5 minutes; finally, after being cooled by the cooling roller with a surface temperature of 20℃, it is wound up under constant tension.
[0103] Comparative Example 1:
[0104] Compared to Example 2, the difference lies in that sodium lignosulfonate, phytic acid, and aniline are not added to the main impregnation solution, and the preparation of the initiator aqueous solution and the atomization initiation operation in the continuous steam oven are not performed. Instead, 4.0 parts by weight of commercially available conductive carbon black powder and 8.0 parts by weight of solid ammonium polyphosphate flame retardant are added to the main impregnation solution, so that the total added mass (12.0 parts by weight) is the same as the total effective mass of 4.0 parts by weight of sodium lignosulfonate, 8.0 parts by weight of 50wt% phytic acid aqueous solution (equivalent to 4.0 parts by weight of effective mass), and 4.0 parts by weight of aniline in Example 2. Physical blending is performed, and the canvas is directly fed into a hot air tenter frame for drying, film formation, and tentering after impregnation. Everything else is the same.
[0105] Comparative Example 2:
[0106] Compared to Example 2, the difference is that the aliphatic nonionic waterborne polyurethane emulsion used in the preparation of the main impregnation solution is replaced in equal amounts with a commercially available conventional aliphatic anionic waterborne polyurethane emulsion. All other aspects are the same.
[0107] Comparative Example 3:
[0108] Compared to Example 2, the difference lies in the omission of the separate preparation of the initiator aqueous solution and the high-pressure atomization spraying operation in the continuous steaming chamber. Instead, the prescribed amount of ammonium persulfate is directly added to the main impregnation solution in the mixing tank at a temperature of 22°C and mixed evenly. The canvas is then impregnated using a co-bath impregnation method with the monomer and initiator. All other aspects remain the same.
[0109] Comparative Example 4:
[0110] Compared with Example 2, the difference is that the supply of direct steam to the continuous steam chamber is stopped, and the saturated hot and humid environment with a temperature of 48°C and a relative humidity of 100% in Example 2 is replaced with a low hot and humid air environment with a temperature of 48°C and a relative humidity of less than 30%. All other aspects are the same.
[0111] Comparative Example 5:
[0112] Compared to Example 2, the difference lies in that, in the room temperature impregnation and liquid retention rate control steps, the roll line pressure of the two-roll mill is significantly increased, reducing the liquid retention rate of the canvas from 80% to 35%. All other aspects are the same.
[0113] Comparative Example 6:
[0114] Compared to Example 2, the difference is that sodium lignosulfonate, as a carbon source, is not added to the preparation of the main impregnation solution, and the corresponding weight gaps are made up with deionized water. Everything else is the same.
[0115] Comparative Example 7:
[0116] Compared to Example 2, the difference lies in that phytic acid (50wt% aqueous solution), which functions as both an acid source and a protic acid, is not added to the preparation of the main impregnation solution. Instead, hydrochloric acid solution is used to adjust the system to the same pH value. All other aspects are the same.
[0117] Test Example 1:
[0118] Take 50 mL of the prepared main impregnation solution of Example 2, Comparative Example 2 and Comparative Example 3 as test samples, and define the time of sampling completion as 0 min.
[0119] The test samples were added to the sample cell of a rotary rheometer equipped with a coaxial cylindrical test fixture, and the test temperature was maintained at 25°C by a constant temperature circulating water bath system.
[0120] The steady-state shear rate of the rotational rheometer was set to 10 s. -1Continuous data acquisition mode was activated to record the change in apparent viscosity of each test sample over time. The test cycle was set to 480 min. When the apparent viscosity of a sample exceeded 1000 mPa·s during the test, and significant gelation or demulsification occurred, resulting in the sample losing its normal flow state, subsequent tests on that group of samples were stopped.
[0121] The experimental data are shown in Table 1:
[0122] Table 1: Data on the change of apparent viscosity of the main impregnation solution at 25°C with standing time
[0123] Settling time (min) Example 2 (mPa·s) Comparative Example 2 (mPa·s) Comparative Example 3 (mPa·s) 0 42.17 185.34 43.82 10 42.53 >1000 (breast breaking) 48.15 30 42.81 - 86.47 60 43.14 - 312.59 120 43.68 - >1000 (gelation) 240 44.12 - - 360 44.59 - - 480 45.26 - -
[0124] Note: "-" in the table indicates that the sample has lost its testing significance or testing has been stopped at that time point.
[0125] in conclusion:
[0126] From Table 1 and Figure 1 The results show that the apparent viscosity of the main impregnating liquid in Example 2 changed from 42.17 mPa·s to 45.26 mPa·s within a 480-minute test period. The viscosity change was small, and no obvious gelation or demulsification occurred during the test, indicating that the main impregnating liquid has good flow stability under the test conditions.
[0127] Comparative Example 2 used an aliphatic anionic aqueous polyurethane emulsion instead of the aliphatic nonionic aqueous polyurethane emulsion used in Example 2. The apparent viscosity of the main impregnation liquid in Comparative Example 2 was 185.34 mPa·s at 0 min, and increased to over 1000 mPa·s within 10 min, while demulsification occurred. This indicates that under the conditions of this test system, the stability of the system was significantly affected when using an anionic aqueous polyurethane emulsion. This phenomenon may be related to the influence of changes in the system's acidity and ionic environment on the colloidal stability of the anionic aqueous polyurethane emulsion. Example 2 used an aliphatic nonionic aqueous polyurethane emulsion, and under the same test conditions, no significant demulsification phenomenon was observed. Its steric hindrance stabilization mechanism may help reduce the impact of acidic and high ionic strength environments on the dispersion stability of the emulsion.
[0128] Comparative Example 3 used a method of adding aniline and ammonium persulfate to the main impregnation solution in the same bath. Its apparent viscosity gradually increased from 43.82 mPa·s at 0 min, with the increase accelerating after 30 min, reaching 312.59 mPa·s at 60 min, and exceeding 1000 mPa·s at 120 min, while gelation also occurred. Considering the preparation method in Comparative Example 3 where aniline and ammonium persulfate were present simultaneously in the main impregnation solution, the aforementioned viscosity changes and gelation phenomenon may be related to the oxidative polymerization of aniline during storage.
[0129] Example 2 involved preparing the main impregnation solution and the initiator aqueous solution separately, and applying the initiator after canvas impregnation to separate aniline and ammonium persulfate during the storage stage of the main impregnation solution. Test results showed that this stepwise application method could reduce the possibility of premature oxidative polymerization during the storage stage to a certain extent, which was beneficial for maintaining the flow stability of the main impregnation solution over a longer period, thus meeting the stability requirements of the working fluid in continuous impregnation processes.
[0130] Test Example 2:
[0131] Wet canvas samples after being rolled out of the groove by a two-roll mill were taken from Example 2 and Comparative Example 5 as test objects.
[0132] Insert the K-type miniature armored thermocouple probe into the sample block in a direction parallel to the surface of the canvas, and position the thermocouple measuring end at the center of the sample block thickness direction; connect the thermocouple probe to the multi-channel temperature data acquisition and recorder, and set the sampling interval to 2s.
[0133] A canvas sample equipped with a thermocouple probe was introduced into a continuous steam chamber at 48°C and 100% relative humidity in a flat state for thermal equilibrium. When the canvas sample reached the area corresponding to the polytetrafluoroethylene (PTFE) atomizing nozzle and began to receive the initiator aqueous solution atomized spray, this moment was set as 0s, and the change in the internal temperature of the canvas sample over time was recorded.
[0134] Temperature changes inside the canvas sample were continuously collected during the in-situ oxidation polymerization process, with a total monitoring time of 360 seconds. The peak temperature and the maximum temperature rise relative to the initial temperature at 0 seconds were determined based on the collected data.
[0135] The experimental data are shown in Table 2:
[0136] Table 2: Data on the change of internal temperature of canvas during the polymerization reaction stage over time
[0137] Reaction time (s) Example 2 Internal Temperature (°C) Example 2: Relative temperature rise (°C) Comparative Example 5 Internal Temperature (°C) Comparative Example 5: Relative temperature rise (°C) 0 48.13 0.00 48.21 0.00 30 49.65 1.52 56.48 8.27 60 52.87 4.74 73.12 24.91 90 56.24 8.11 89.34 41.13 120 59.88 11.75 95.17 46.96 150 61.42 13.29 82.59 34.38 180 60.75 12.62 71.38 23.17 240 59.16 11.03 61.44 13.23 300 58.23 10.10 55.72 7.51 360 57.51 9.38 51.85 3.64
[0138] in conclusion:
[0139] According to the results shown in Table 2, the internal temperature of the canvas sample in Example 2 gradually increased from 48.13℃ at 0s to 61.42℃ at 150s, and then gradually decreased. The maximum temperature rise relative to the initial temperature during the test period was approximately 13.29℃. The internal temperature of the canvas sample in Comparative Example 5 increased more rapidly from 48.21℃ at 0s to 95.17℃ at 120s, with a maximum temperature rise relative to the initial temperature of approximately 46.96℃. Its temperature rise rate and peak temperature rise were both higher than those of Example 2.
[0140] The main difference between Example 2 and Comparative Example 5 lies in the liquid retention rate after impregnation. The liquid retention rate in Example 2 was 80%, while that in Comparative Example 5 was 35%. The higher liquid retention rate allows more liquid phase medium to remain inside the canvas. Since water has a large specific heat capacity, this liquid phase environment may absorb and buffer the heat generated during the oxidative polymerization process, thus making the temperature change inside the canvas relatively gradual.
[0141] Meanwhile, under the condition that the amount of initiator aqueous solution sprayed remains constant according to the dry fabric mass, the amount of aniline carried in the canvas in Comparative Example 5 is reduced due to the decrease in the amount of main impregnation solution, which may lead to a change in the actual ratio of ammonium persulfate to aniline. Therefore, the large temperature rise observed in Comparative Example 5 may be related to factors such as the decrease in the liquid phase content inside the canvas and the change in the relative ratio of oxidant to aniline, and based on the test results, it is not appropriate to attribute it to a single factor.
[0142] Temperature variations during in-situ oxidative polymerization can affect the formation state of polyaniline. Example 2, under the test conditions, exhibited a lower peak temperature and a more gradual temperature rise, indicating that maintaining a high liquid content in the canvas helps to slow down the rapid increase in local temperature during the in-situ oxidative polymerization stage and helps to maintain a relatively stable reaction temperature environment.
[0143] Test Example 3:
[0144] The modified layers were peeled off and collected from the canvas substrates of Examples 2, 6, and 7 after drying, film formation, and stretching. The obtained modified layers were ground and passed through a 200-mesh stainless steel standard sieve, followed by centrifugal washing with anhydrous ethanol and deionized water, three times each. The washed samples were placed in a vacuum drying oven and dried at 60°C and 0.08 MPa for 12 hours to obtain modified layer powder test samples.
[0145] Weigh 2.1 mg of the modified layer powder sample obtained in Example 2 and 198.5 mg of thoroughly dried potassium bromide powder, mix and grind them thoroughly in an agate mortar, and then press them into a tablet at 15 MPa for 2 minutes to obtain a test sheet. Place the obtained sheet in the sample chamber of a Fourier transform infrared spectrometer for testing, with a scanning wavenumber range of 4000–400 cm⁻¹. -1 The resolution is 4cm. -1 The cumulative number of scans was 32, and the infrared spectrum was recorded.
[0146] Weigh out 5.3 mg, 5.1 mg, and 5.4 mg of the modified layer powder samples from Examples 2, 6, and 7, respectively, place them in alumina crucibles, and then place them in a thermogravimetric analyzer. The test was conducted under a high-purity nitrogen atmosphere, with both the protective gas and microflow gas flow rates set to 50 mL / min. The programmed heating rate was 10 °C / min, and the test temperature range was 30–800 °C. The change in the residual mass of the sample with temperature during the heating process was recorded.
[0147] The experimental data are shown in Table 3:
[0148] Table 3: Residual mass fraction data of modified layer powder at different test temperatures
[0149] Test temperature (°C) Example 2 (%) Comparative example 6% Comparative example 7 (%) 50 99.82 99.75 99.85 150 98.13 97.46 98.61 250 94.67 92.83 95.72 350 88.21 82.51 90.14 450 75.48 62.17 68.39 550 66.83 47.92 51.26 650 62.14 40.28 44.53 800 56.45 33.18 37.52
[0150] in conclusion:
[0151] According to Table 3 and by Figure 2 As shown in (a) the Fourier transform infrared spectrum, the modified layer obtained in Example 2 has a wavelength of 1570 cm⁻¹. -1 and 1495cm -1 An absorption peak appears nearby, corresponding to the characteristic absorptions of the polyaniline quinone and benzene structures; at 1298 cm⁻¹ -1 and 1140cm -1 Absorption signals related to C-N bond vibrations and the protonated polyaniline structure can also be observed nearby. These absorption characteristics correspond well with the typical spectral characteristics of polyaniline and can be used as a characterization basis for the formation of polyaniline structures in the modified layer.
[0152] Furthermore, at 1045cm -1 and 980cm -1 Absorption signals associated with phosphorus-containing groups can be observed nearby. Combined with the composition and process conditions of the phytic acid modification treatment in Example 2, the above spectroscopic results indicate the presence of phosphorus-containing structures in the modified layer, providing a certain spectroscopic characterization basis for the participation of phytic acid in the protonation doping process of polyaniline. Since infrared spectroscopy mainly reflects the vibrational absorption characteristics of functional groups and chemical structures in the system, non-covalent interactions such as ionic interactions and hydrogen bonds that may exist between phytic acid and polyaniline segments can be analyzed in conjunction with the system composition and related spectral characteristics, rather than being directly determined as structural relationships from a single infrared spectral result.
[0153] From Table 3 and Figure 2As shown in (b), Examples 2, 6, and 7 all exhibited varying degrees of mass loss in the low to medium temperature range; as the test temperature further increased, the differences in residual mass among the samples gradually increased. In the higher temperature range of 450–800°C, the residual mass fraction of Example 2 was generally higher than that of Comparative Examples 6 and 7. At 800°C, the residual mass fraction of Example 2 was 56.45%, while that of Comparative Examples 6 and 7 was 33.18% and 37.52%, respectively.
[0154] Comparative Example 6, without the addition of sodium lignosulfonate, had a lower high-temperature residual mass fraction than Example 2, indicating that the introduction of sodium lignosulfonate is related to the formation and retention of high-temperature residues in the system. Comparative Example 7, using hydrochloric acid to adjust the pH of the system without the addition of phytic acid, also had a lower residual mass fraction in the temperature range above 450°C than Example 2, suggesting that the phosphorus-containing structure provided by phytic acid, in addition to its acidic adjustment effect, may also affect the formation of residues during the heating process.
[0155] Test Example 4:
[0156] From 600g / m 2 800g / m 2 and 1200g / m 2 Test samples were taken from the unmodified raw fabric and the canvas substrates of Examples 1, 2, 3, and Comparative Example 1, which had undergone drying, film formation, and stretching. The basis weight was 600 g / m². 2 The unmodified original fabric was used as the base fabric in Example 1, with a basis weight of 800 g / m². 2 The unmodified original fabric, used as the base fabric for Example 2 and Comparative Example 1, had a basis weight of 1200 g / m². 2 The unmodified original fabric was used as the base fabric for Example 3. Strips with warp and weft dimensions of 250mm × 25mm were cut and placed in a standard atmospheric environment with a temperature of 20°C and a relative humidity of 65% for 24 hours for conditioning.
[0157] Bending stiffness was tested using a fabric stiffness tester. The conditioned strip was placed flat on the test platform and advanced towards the incline at a set speed. The extension length was recorded when the drooping tip of the strip touched the test inclination scale line. The warp and weft bending stiffness of the sample were calculated based on the extension length and the sample's linear density. Five tests were performed on each group of samples, and the arithmetic mean was taken.
[0158] The fracture strength was tested using a universal testing machine. The clamping distance was set to 200 mm and the tensile speed to 100 mm / min. The two ends of the strip were fixed in the upper and lower clamps and the test was started. The specimen was stretched until it fractured, and the maximum force at which the specimen fractured in the longitudinal direction was recorded, which is the longitudinal fracture strength.
[0159] The warp tensile strength values recorded in the examples and comparative examples were divided by the warp tensile strength values of the unmodified original fabric with the same basis weight to calculate the percentage of tensile strength retention for each sample. In Example 1, the warp tensile strength was 600 g / m². 2 Using the unmodified virgin fabric as the calculation basis, Example 2 and Comparative Example 1 were calculated at 800 g / m². 2 Using the unmodified original fabric as the calculation basis, Example 3 uses 1200 g / m 2 The unmodified original fabric was used as the calculation basis.
[0160] The experimental data are shown in Table 4:
[0161] Table 4: Test Results of Physical and Mechanical Properties of Canvas Substrate
[0162] Group <![CDATA[Base fabric weight (g / m 2 )]]> Meridional bending stiffness (mN·m) Woven bending stiffness (mN·m) Meridional fracture strength (N) Fracture strength retention rate (%) <![CDATA[600g / m 2 Original fabric 600 33.15 29.84 4094.1 - Example 1 600 41.27 38.45 3946.8 96.4 <![CDATA[800g / m 2 Original fabric 800 34.82 31.65 4150.2 - Example 2 800 42.61 39.12 4012.3 96.7 Comparative Example 1 800 135.82 128.43 2685.1 64.7 <![CDATA[1200g / m 2 Original fabric 1200 38.62 35.71 4171.3 - Example 3 1200 45.38 42.06 4058.7 97.3
[0163] Note: "-" in the table indicates that the corresponding unmodified original fabric is used as the reference sample and the tensile strength retention rate is not calculated.
[0164] in conclusion:
[0165] According to the data in Table 4, after modification, the warp and weft bending stiffness of the canvas substrates in Examples 1 to 3 only changed to a limited extent compared with the unmodified original fabric of the same weight, indicating that the modification treatment did not cause significant fabric stiffening. The breaking strength retention rates of Examples 1, 2, and 3 were calculated based on 600 g / m². 2 800g / m 2 and 1200g / m 2 The warp tensile strength of the unmodified original fabric was calculated. Comparative Example 1, which underwent physical blending with commercially available conductive carbon black powder and solid ammonium polyphosphate flame retardant, showed a dramatic increase in warp flexural stiffness to 135.82 mN·m, indicating severe structural hardening, which was significantly higher than that of the same basis weight 800 g / m. 2 The original fabric, without modification, had a tensile strength retention rate of 64.7%.
[0166] The impregnation solution used in Comparative Example 1, containing solid particles, had a higher apparent viscosity due to its high content of insoluble particles, making it difficult for the slurry to fully penetrate the yarn and inter-fiber pores during padding. Resin and powder fillers tended to accumulate on the surface of the canvas, forming a continuous resin-rich layer after hot air setting. This surface-rich resin layer not only increased the sample's stiffness against bending deformation but also potentially caused localized stress concentration under tensile stress, leading to premature breakage of the main load-bearing fibers.
[0167] The low-viscosity aqueous impregnation system used in the embodiment does not contain any added insoluble solid powder and exhibits good flowability. The main impregnation liquid penetrates into the internal pores of the yarn and fibers, and initiates in-situ oxidation polymerization of aniline on the surface of the fiber monofilament through a steam environment, forming a coating structure at the fiber monofilament scale. This does not damage the original three-dimensional interweaving state and stress transmission path of the fabric, and maintains the stability of the physical and mechanical properties of the substrate.
[0168] Test Example 5:
[0169] Square samples with a size of 100mm×100mm were cut from the canvas substrates after drying, film formation and stretching in Examples 1 to 3, and Comparative Examples 4 and 5. Two sets of samples were prepared for each group and placed in a standard atmospheric environment with a temperature of 20°C and a relative humidity of 65% for 24 hours to adjust the humidity.
[0170] A concentric ring electrode surface resistivity tester was used to test the surface resistivity of both sides of the first set of samples under standard test conditions. The test electrode was pressed flat on the sample surface, a DC test voltage of 100V was applied, and the data was read and recorded after 15 seconds. The logarithmic average of three test results was taken to obtain the initial surface resistivity of the front and back sides.
[0171] The second set of samples was placed in a standard washing test machine, standard detergent was added, the water temperature was set to 40℃, and 50 washing cycles were performed continuously according to the standard textile washing procedure. After washing, the samples were removed, laid flat to dry, and then placed in a standard atmospheric environment for 24 hours to acclimate.
[0172] Using the same equipment and parameters as in step 2, the surface resistivity of the front side of the second set of samples after water washing and conditioning was tested, and the logarithmic value of the surface resistivity after water washing was read and recorded.
[0173] The experimental data are shown in Table 5:
[0174] Table 5: Surface Resistivity Test Data of Canvas Substrates in Examples and Comparative Examples
[0175] Group <![CDATA[Initial front surface resistivity (Log 10 Ω)]]> <![CDATA[Initial back surface resistivity (Log 10 Ω)]]> <![CDATA[Front surface resistivity after 50 washes (Log 10 Ω)]]> Example 1 5.62 5.68 5.81 Example 2 5.45 5.49 5.66 Example 3 5.18 5.23 5.36 Comparative Example 4 4.08 7.95 10.65 Comparative Example 5 11.75 11.79 11.94
[0176] in conclusion:
[0177] According to the data in Table 5, the initial logarithmic values of the surface resistivity on both sides of Examples 1 to 3 were all between 5.1 and 5.7, with a small difference, indicating that the conductive network was uniformly distributed in the thickness direction of the substrate. After 50 standard water washes, the surface resistivity only increased slightly, remaining within the antistatic judgment range used in this test (surface resistivity less than 1×10⁻⁶). 8(Ω), indicating a stable bonding strength. Comparative Example 4 was treated in a low-humidity and hot air environment. Its initial front surface resistivity was as low as 4.08, while the reverse side was as high as 7.95, showing a significant difference between the front and reverse sides. After washing with water, the resistivity suddenly increased to 10.65, and the antistatic function was lost.
[0178] This is because during hot air drying, moisture evaporates rapidly on the surface, and the internal liquid, driven by capillary pressure and concentration gradient, migrates towards the evaporation interface, carrying some water-soluble components to the surface for enrichment. This migration phenomenon causes polyaniline and dopants to tend to accumulate on the surface, reducing their uniformity of distribution along the fabric thickness and their bonding with deeper fibers. During washing, the free conductive material on the surface is easily detached.
[0179] Comparative Example 5, due to its low liquid carryover rate, exhibited a significant and rapid temperature rise during the reaction initiation stage, with an initial surface resistivity of 11.75, demonstrating low conductivity. Considering the weakened liquid-phase heat capacity buffering effect and the increased actual ratio of ammonium persulfate to aniline in Comparative Example 5, it is speculated that localized high temperature and a relatively excessive oxidant may jointly cause excessive oxidation of polyaniline segments or damage to the conjugated structure, thereby reducing its conductivity. The embodiment employed a continuous steaming environment with 100% relative humidity, significantly reducing evaporation-driven moisture migration and the capillary migration of water-soluble components to the surface. Combined with the heat capacity buffering established by the high liquid carryover rate, this facilitated in-situ oxidative polymerization of polyaniline on the surface of the fiber monofilaments, achieving uniform and durable antistatic performance within the fabric.
[0180] Test Example 6:
[0181] Samples were taken from the dried and stretched canvas substrates of Examples 1 to 3, Comparative Examples 1, 4, 6, and 7. Samples were cut to 150mm × 58mm according to the limiting oxygen index test standard, and to 300mm × 89mm according to the vertical burning test standard. Ten samples were prepared in parallel for each group. Five samples were used as initial state test samples, and the other five were subjected to 50 consecutive water washing cycles in a standard washing machine and then dried. All test samples were conditioned for 24 hours at 20°C and 65% relative humidity.
[0182] The limiting oxygen index (LOI) tester was used to test the samples. The samples were vertically fixed in the combustion chamber, and a set oxygen-nitrogen mixture was introduced and the top of the samples was ignited using an igniter. The combustion of the samples was observed and the minimum oxygen concentration (by volume) required to maintain stable combustion of the samples was recorded. The arithmetic mean of five tests was taken as the limiting oxygen index test result.
[0183] The combustion state of the samples was determined using a vertical combustion tester. The sample was suspended on the test stand, and a standard flame was used to ignite it at the center of the bottom edge of the sample for 12 seconds before the flame was removed. The duration of flaming combustion was recorded as the afterflame time, and the duration of smoldering without flame was recorded as the smoldering time.
[0184] The limiting oxygen index (LOI) test in step 2 was repeated on the spare samples that had undergone 50 water washing cycles to obtain the LIO after washing. The LIO retention rate was calculated by dividing the LIO after washing by the initial LIO.
[0185] The experimental data are shown in Table 6:
[0186] Table 6: Test data on flame retardant properties and washability of canvas substrates in the examples and comparative examples
[0187] Group Initial limiting oxygen index (%) Afterburn time (s) Smoldering time (s) Limiting oxygen index (%) after 50 washes Limiting oxygen index retention (%) Example 1 32.4 2.1 1.8 31.1 96.0 Example 2 34.6 0.8 0.5 33.5 96.8 Example 3 35.8 0.0 0.0 34.7 96.9 Comparative Example 1 31.5 3.5 4.2 24.2 76.8 Comparative Example 4 33.1 1.6 2.3 23.5 71.0 Comparative Example 6 25.3 12.4 15.6 24.1 95.3 Comparative Example 7 26.8 8.9 11.2 25.6 95.5
[0188] in conclusion:
[0189] According to the data in Table 6, the initial limiting oxygen index (LOI) of Examples 1 to 3 all reached over 32%, exhibiting extremely short afterflame and smoldering times in vertical combustion tests. Example 3 even achieved a 0-second afterflame and smoldering state, demonstrating flame-retardant and self-extinguishing characteristics. After 50 standard water washes, the LIO retention rate remained above 96%. Comparative Example 1 used a powder blending process, and Comparative Example 4 used low-humidity hot air treatment. Due to the migration phenomenon, components migrated to the surface. Although both examples achieved a certain LIO in the initial state, the flame-retardant components were mostly present in a surface-enriched or physically bound state, unable to resist the mechanical force of water washing, resulting in the LIO retention rates decreasing to 76.8% and 71.0% respectively after washing.
[0190] Comparative Example 6 did not contain sodium lignosulfonate, thus lacking the aromatic char-forming carbon source in the flame-retardant system; Comparative Example 7 did not contain phytic acid, thus lacking the acid source and phosphorus-containing flame-retardant components. Due to the lack of core components constituting the phosphorus / nitrogen / carbon synergistic flame-retardant system, the two comparative examples failed to adequately promote dehydration, cross-linking, and char formation upon heating, resulting in a weakened barrier effect on heat transfer and oxygen diffusion. Consequently, their initial limiting oxygen indices were only 25.3% and 26.8%, respectively, and their afterflame and smoldering times were significantly prolonged. The examples utilize liquid-phase impregnation combined with in-situ polymerization technology to promote the formation of a phosphorus / nitrogen / carbon synergistic flame-retardant system by phytic acid, sodium lignosulfonate, and polyaniline on the surface and within the pores of the fiber monofilaments.
[0191] Although Comparative Examples 6 and 7 still exhibited high limiting oxygen index (LOI) retention rates, their initial LIOs were significantly lower than those of the Examples, indicating that sodium lignosulfonate and phytic acid play a crucial role in improving the absolute level of the system's flame retardant performance. The water-washable durability demonstrated in the Examples is related to in-situ deposition, aqueous polyurethane film formation, and the ionic, hydrogen bond, and interfacial interactions between the components and fibers. During combustion, phosphorus-containing components promote dehydration and char formation, sodium lignosulfonate provides an aromatic char source, and nitrogen-containing polyaniline participates in synergistic char formation, thereby promoting the formation of a char layer with heat insulation and oxygen barrier properties, resulting in stable flame retardant performance.
[0192] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification, characterized in that, Includes the following steps: Sodium lignosulfonate, phytic acid aqueous solution, aniline, aliphatic nonionic waterborne polyurethane emulsion and deionized water are mixed evenly to obtain the main impregnation solution. Ammonium persulfate was dissolved in deionized water to obtain an initiator aqueous solution; The canvas is continuously and flatly passed through the main impregnation liquid for immersion and then squeezed through a rolling mill to control the liquid content. The canvas, after being squeezed by the rolling mill, is introduced into a continuous steam chamber. Under the influence of steam, the initiator aqueous solution is atomized into droplets and sprayed onto the canvas surface to carry out an in-situ oxidative polymerization reaction. The canvas that has completed in-situ polymerization is introduced into a hot air tenter frame for drying and film formation, and then wound up after cooling.
2. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, The main impregnation solution is prepared by mixing raw materials comprising the following parts by weight: Sodium lignosulfonate 3.0-5.0 parts; phytic acid aqueous solution 6.0-10.0 parts; aniline 3.0-5.0 parts; aliphatic nonionic waterborne polyurethane emulsion 15.0-20.0 parts; deionized water 60.0-73.0 parts; The initiator aqueous solution is prepared by mixing the following raw materials in parts by weight: 30.0-40.0 parts ammonium persulfate; 60.0-70.0 parts deionized water.
3. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, The phytic acid aqueous solution contains 50 wt% phytic acid. The canvas is an industrial canvas made of pitch-based chopped carbon fiber and flame-retardant polyester fiber, with a basis weight of 600-1200 g / m². 2 .
4. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, The aliphatic nonionic aqueous polyurethane emulsion is prepared from raw materials comprising the following parts by weight: 45.0-55.0 parts of polycarbonate diol; 10.0-20.0 parts of polyethylene glycol; Isophorone diisocyanate 16.7-22.2 parts; 0.04-0.06 parts of dibutyltin dilaurate; 3.5-5.3 parts of 1,4-butanediol; 340.8-370.0 parts of deionized water.
5. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 4, characterized in that, The preparation method of the aliphatic nonionic aqueous polyurethane emulsion includes the following steps: The polycarbonate diol and the polyethylene glycol are added to a reaction vessel and dehydrated under vacuum at 100-110°C for 1-2 hours. Cool to 60-65℃, add the isophorone diisocyanate, then heat to 75-85℃, add the dibutyltin dilaurate dropwise, and react at a constant temperature for 2-3 hours; The temperature was lowered to 40-50℃, and the 1,4-butanediol was added to carry out a chain extension reaction for 1-1.5 hours. During the addition of the deionized water, a high shear dispersion of 2000-3000 rpm was maintained. The deionized water was slowly added and reverse emulsification was carried out. The dispersion was continued for 30-45 minutes to obtain an aliphatic nonionic waterborne polyurethane emulsion with a solid content of 20wt%.
6. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, When preparing the main impregnation solution, mechanical stirring is turned on at a temperature of 20-25℃, the speed is set to 300-500 rpm, and the mixture is continuously mixed for 30-45 minutes. When preparing the initiator aqueous solution, it is stirred and dissolved at room temperature in the dark to form a homogeneous transparent liquid.
7. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, The linear speed for impregnating the canvas is set to 10-15 m / min, and the impregnation temperature is controlled at 20-25℃. By adjusting the linear pressure of the rollers, the liquid content of the canvas is controlled at 75%-85%.
8. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, Direct steam is introduced into the continuous steam chamber, the temperature is maintained at 45-50℃, and the relative humidity is kept constant at 98%-100%; the residence time of the canvas in the steam chamber is set to 5-8 minutes.
9. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, When the initiator aqueous solution is atomized into droplets and sprayed onto the canvas surface, it is done through polytetrafluoroethylene airflow atomizing nozzles distributed above and below the canvas running trajectory. The atomization operation pressure is set to 0.2-0.3MPa, and the atomized droplet particle size is controlled at 10-50μm. The spraying amount of the initiator aqueous solution is adjusted to 18%-25% of the dry fabric mass.
10. The method for preparing flame-retardant and antistatic canvas substrate by fiber impregnation and coating modification according to claim 1, characterized in that, When drying and forming film in the hot air tenter frame, the temperature of the hot air zone is set to 120-130℃, and the canvas stay time is 3-5 minutes; after cooling and winding, contact cooling is performed using a cooling roller with a surface temperature of 15-20℃, and constant tension winding is performed.